The Transformation of Accounting Practices in the Era of Artificial Intelligence: An Analysis of the Role of Artificial Intelligence in Enhancing Financial Reporting Quality and Business Decision-Making - Tikkos Sitanggang (Dhana, 2026)
The rapid advancement of digital technologies has significantly transformed accounting practices, particularly through the adoption of artificial intelligence (AI). The integration of AI in accounting systems has shifted the role of accounting from routine transactional processing to a more strategic function that supports financial reporting quality and data-driven business decision-making. This study aims to analyze the role of artificial intelligence in transforming accounting practices by improving the quality of financial reporting and supporting strategic managerial decisions. The study employs a qualitative approach using a systematic literature review method. Data were collected from peer-reviewed journal articles related to artificial intelligence, digital accounting transformation, financial reporting quality, and decision support systems published between 2021 and 2025. The collected literature was analyzed through thematic and conceptual synthesis to identify patterns and relationships between AI adoption, financial reporting quality, and business decision-making processes. The findings indicate that artificial intelligence technologies such as machine learning, robotic process automation, and predictive analytics improve financial reporting accuracy, timeliness, and transparency while also enhancing fraud detection and internal control mechanisms. In addition, AI-driven analytics enable organizations to generate predictive insights that support strategic planning, risk management, and business decision-making. The study concludes that artificial intelligence plays a transformative role in modern accounting systems by improving financial reporting quality and strengthening the strategic function of accounting information in organizational decision-making.